Epidemiology of traumatic spinal cord injury in Nepal: A systematic review - Parajuli, Bikash; Acharya, Khagendra; Shrestha, Dipak (Asian Journal of Medical Sciences, 2020)
Spinal cord injury (SCI) leads to disabling condition. In Nepal the nationwide statistics of incidence and prevalence of SCI is still unclear which demands a systematic examination of crucial epidemiological aspects of SCI. An electronic search was conducted on PubMed, Ovid EMBASE, Cochrane Library and Google Scholar. Clinical studies investigating epidemiology of spinal cord injury were included. A narrative synthesis of the data that comprised 1796 patients was conducted. Males comprised 73%, and the mean age varied from 32 to 47 years. The two leading causes of SCI were falls (60%) and accidents (17%). Most patients had incomplete neurology (AIS grade B, C and D = 42%) followed by AIS A grade (36.3%). Cervical injury (37.4%) was the most common level of injury. Mortality during hospital stay was low (1.98%) whereas after rehabilitation was high (24.32%). The review contributes in understanding epidemiology of SCI in Nepal which is expected to help in planning for prevention and management.